2010
DOI: 10.1071/sr10036
|View full text |Cite
|
Sign up to set email alerts
|

Stability and stabilisation of biochar and green manure in soil with different organic carbon contents

Abstract: Abstract. Due to its recalcitrance against microbial degradation, biochar is very stable in soil compared to other organic matter additions, making its application to soils a suitable approach for the build-up of soil organic carbon (SOC). The net effects of such biochar addition also depend on its interactions with existing organic matter in soils. A study was established to investigate how the status of pre-existing soil organic matter influences biochar stabilisation in soil in comparison to labile organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(135 citation statements)
references
References 49 publications
8
126
1
Order By: Relevance
“…A change in N partitioning associated with a decrease in soil nitrification is strongly implicated because the biochar-only treatment maximized the soil NH 4 / NO 3 concentration ratio (Supplemental Table S1) relative to other treatments on average. The overall effect of these changes would result in the apparent stabilization of soil C (Kimetu and Lehmann, 2010). The decreased root biomass of biochar-only treatment (Fig.…”
Section: Mechanism By Which Biochar Effects Soil Processesmentioning
confidence: 99%
“…A change in N partitioning associated with a decrease in soil nitrification is strongly implicated because the biochar-only treatment maximized the soil NH 4 / NO 3 concentration ratio (Supplemental Table S1) relative to other treatments on average. The overall effect of these changes would result in the apparent stabilization of soil C (Kimetu and Lehmann, 2010). The decreased root biomass of biochar-only treatment (Fig.…”
Section: Mechanism By Which Biochar Effects Soil Processesmentioning
confidence: 99%
“…Other researches showed that biochar application could led to an increase of CO 2 emission from SOC-rich soil [13]. When applied pasture waste biochar(10 t·hm -2 ) into soil, it showed increased CO 2 and N 2 O emission than CK whereas net absorption of CH 4 [14].…”
Section: Recentlymentioning
confidence: 99%
“…However, there are some reports about the biochar related to products of short duration pyrolysis at higher temperatures known as"fast pyrolysis"and even novel techniques such as microwave conversion. During the process of production of biochar, the transformation from energy to heat is relatively low which resulted in high storage of carbon in biochar and significantly low emissions of global warming gases into atmosphere [6].…”
Section: The Characteristics Of Biocharmentioning
confidence: 99%